Periodontal disease and smoking: Systematic review - Naif Alwithanani (Wolters Kluwer Medknow Publications, 2023)
Introduction: Tobacco has been linked multiple times to many health implications. The relationship between periodontitis and tobacco was thoroughly investigated in this systemic review to evaluate if tobacco specifically smoking impacts the progression of periodontal through impairing vascular and immunity mediators processes. Materials and Methods: The manual and electronic literature searches up to 2020 in the databanks of the EMBASE, MEDLINE, PUBMED, and SCOPUS were conducted. The search terms were "periodontitis," "periodontitis diseases," "smoking," "tobacco use," "tobacco," and "cigarette, pipe, and cigar." The types of studies included were restricted to the original studies and human trials. Analyses of subgroups and meta-regression were used to calculate the heterogeneity. Results: 15 papers total were considered in the review, however only 14 of them provided information that could be used in the meta-analysis. Smoking raises the incidence of periodontitis by 85% according to pooled adjusted risk ratios (risk ratio 1.845, CI (95%) =1.5, 2.2). The results of a meta-regression analysis showed that age, follow-up intervals, periodontal disease, the severity of periodontitis, criteria used to determine periodontal status, and loss to follow-up accounted for 54.2%, 10.7%, 13.5%, and 2.1% of the variation in study results. Conclusion: Smoking has an undesirable impact on periodontal incidence and development. Therefore, when taking the history of the patients at the initial visits the information about the habit of smoking has to be thoroughly noted.